Recovery from ‘schizophrenia’: Perspectives of mental health nurses in the Eastern island of Indonesia - Tasijawa, Fandro Armando; Suryani, Suryani; Sutini, Titin; Maelissa, Sinthia Rosanti (Belitung Nursing Journal, 2021)
Background: Recovery is a way of life to make people’s lives more meaningful by working and interacting socially in the community. The recovery has become a new vision of mental health services, including in persons with schizophrenia. However, this concept is relatively new and still limited to nurses in developing countries, such as Indonesia. Several studies among nurses related to this topic have been conducted in the Western part of Indonesia. Yet, no studies have been implemented in the Eastern part of Indonesia. Therefore, exploring nurses’ perspectives in the Eastern island of Indonesia is necessary to provide a complete understanding of recovery in patients with schizophrenia.Objective: To explore the perspectives of mental health nurses on recovery from schizophrenia. Methods: This was a qualitative study using a phenomenological design. The study was conducted from April to May 2020 at community health centers in Maluku, Indonesia. Eight nurses recruited using purposive sampling participated in in-depth interviews. The interviews were audio-recorded, transcribed verbatim, validated, and analyzed based on Colaizzi’s method of data analysis.Results: Five themes were generated, including (i) treat a patient like a brother, (ii) recovery as an unfamiliar term with various meanings, (iii) medication as the primary action but also the main problem, (iv) being recovered if referred to a mental hospital, and (v) ineffective mental health programs.Conclusion: The findings of this study can be used as an input and evaluation for nurse managers to make an effort to uniform the perception among nurses in Indonesia regarding the recovery process in schizophrenia. It is also suggested that community health centers leaders and mental health policymakers prioritize and optimize recovery-oriented mental health programs and services in the Eastern island of Indonesia. Additionally, the findings offer new insight about ‘we are brothers’ or called ‘hidop orang basudara’, which is expected to be one motto for nursing care in Indonesia and beyond.